Persistent inpatient delirium associated with increased length of stay and mortality - Jerry Bradley; Fei Tang; Zachary Panzarella; Jacob Nanney; Iriana Hammel; Bill Bryant; Darby Cole (PLoS ONE, 2025)
Introduction Delirium is associated with an increased risk of post-hospitalization mortality. However, the impact of persistent delirium on mortality is not well defined. Methods We conducted a retrospective cohort study on the association of non-persistent or persistent delirium and mortality. We included patients aged > 65 years admitted to the Owensboro Health Regional Hospital between August 2021 and August 2022. Delirium was determined based on a score of ≥ 2 on the Nurse Delirium Screening Scale (NuDESC) recorded on all admitted patients three times a day during nursing shift change. Multivariate logistic regression models were used to evaluate the association between non-persistent or persistent delirium and 30-day, 60-day, 90-day, 180-day, and 360-day mortality after adjusting for covariates. Sensitivity analysis was performed to compare different definitions of delirium as ≥ 2, ≥ 3, or ≥ 4 days of delirium occurring consecutively or non-consecutively. Results 4560 hospitalized patients were included in this study. Of these, 634 (13.9%) were identified as having delirium (persistent or non-persistent) and 3926 (86.1%) as without delirium. Patients with delirium were slightly older than those without (77 ± 7.9 vs. 79.5 ± 8.5 years old). The patients in each group were relatively comparable in terms of sex, race, smoking status, Medicare user status, and comorbidities. After adjusting for comorbidities, delirium was associated with an increase of mortality at 30 days for patients with persistent delirium of 2 days (aOR 4.88, 95% CI 3.63–6.54), 3 days (aOR 5.64, 95% CI 3.95–7.98), 4 days (aOR 7.21, 95% CI 4.74–10.8). Persistent delirium was associated with higher 60-day, 90-day, 180-day, and 360-day mortality rates, with an incremental increase in the risk of mortality for each additional day of delirium. Conclusion Persistent delirium is consistently associated with increased mortality, with an increased risk of mortality for each additional day of delirium, underscoring the need for early identification and treatment.